A comparision on initial-value ray tracing and fast marching eikonal solver for VTI traveltime computing - S.Y.M Alashloo, Deva Ghosh, YasirBashir, W. I. Wan Yusoff, . (2015)
The Earth's subsurface is an anisotropic medium where the velocity of seismic waves alters in different propagation angles. Omitting anisotropy in seismic imaging not only brings mis-positioning of migrated dipping events but also fails to retain dipping energy during dip-moveout. To account for the efficacy of seismic anisotropy in imaging, an anisotropic wave equation must be engaged.